Пошаговое объяснение:
x = 0,35; y = 0,2
0,4х – 0,012 : у = 0,14 - 0,06 = 0,08
x = 1,4; y = 6.
0,4х – 0,012 : у = 0,56 - 0,002 = 0,558
а) х = 0,35; у = 0,2
0,4х - 0,012 : у = 0,4 * 0,35 - 0,012 : 0,2 =
0,14 - 0,06 = 0,08
б) х = 1,4; у = 6
0,4х - 0,012 : у = 0,4 * 1,4 - 0,012 : 6 =
0,56 - 0,002 = 0,558
Пошаговое объяснение:
x = 0,35; y = 0,2
0,4х – 0,012 : у = 0,14 - 0,06 = 0,08
x = 1,4; y = 6.
0,4х – 0,012 : у = 0,56 - 0,002 = 0,558
Пошаговое объяснение:
а) х = 0,35; у = 0,2
0,4х - 0,012 : у = 0,4 * 0,35 - 0,012 : 0,2 =
0,14 - 0,06 = 0,08
б) х = 1,4; у = 6
0,4х - 0,012 : у = 0,4 * 1,4 - 0,012 : 6 =
0,56 - 0,002 = 0,558